Privacy Anxiety on Micro-Influencers in Self-Disclosure through the Add Yours on Instagram Social Media - Alfi Hasanah Siregar (Budapest International Research and Critics University, 2022)
Instagram is a social media platform with the fourth most users worldwide. This application provides various features and facilities. The available features and facilities allow users to do many things, including revealing themselves using their social media. However, 40.6% of users think that social media user is not safe. This insecurity arises as a result of privacy being violated when self-disclosure. This causes social media users to experience privacy anxiety. The theory of Communication Privacy Management by Sandra Petronio is used to analyze this research. This study uses a qualitative method with a phenomenological approach to rely entirely on the informant's thoughts about the situation or event he experienced. Primary data were collected through structured interviews and secondary data from a literature study. Two informants in this research are micro-influencers on Instagram. Informants were obtained using a purposive sampling technique. The criteria included a micro-influencer, had used the add yours and lived in Medan. The results show that the add yours can cause privacy concerns for micro-influencers. There are two types of motivation in self-disclosure through the add yours, namely personal experience and the experience of others. Anxiety levels were also higher in individuals who had personal experiences of privacy abuse. Just as privacy can free individuals from sharing information with others, individuals can decide what to disclose and keep private, so privacy concerns depend on individual control & ownership of Instagram.